The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/dddt.s260419
|View full text |Cite
|
Sign up to set email alerts
|

<p>Enhancing the Butyrylcholinesterase Activity in HEK-293 Cell Line by Dual-Promoter Vector Decorated on Lipofectamine</p>

Abstract: Purpose: Human butyrylcholinesterase (BChE) serves as a bio scavenger to counteract organophosphate poisoning. It is also a potential drug candidate in several therapeutic fields. Therefore, in the present study, we constructed a new dual-promoter plasmid consisting of Cytomegalovirus (CMV) and human elongation factor 1α (EF-1α) promoters and transfected that into HEK-293 cells using Lipofectamine to enhance the BChE secretion. Methods: The new dual-promoter construction (pBudCE dual BChE) including two copies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Referring to reference [ 29 ], the GLUT4 promoter recombinant plasmid was constructed using pEGFP-N1 plasmid as the vector, the CMV promoter of pEGFP-N1 plasmid was replaced by the GLUT4 promoter using double enzyme digestion (see Figure 7 a). Rat GLUT4 (Slc2a4, NM_012751) sequences of its gene starting area (−2300–100bp) were extracted from the EPD website ( ) accessed on 28 September 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Referring to reference [ 29 ], the GLUT4 promoter recombinant plasmid was constructed using pEGFP-N1 plasmid as the vector, the CMV promoter of pEGFP-N1 plasmid was replaced by the GLUT4 promoter using double enzyme digestion (see Figure 7 a). Rat GLUT4 (Slc2a4, NM_012751) sequences of its gene starting area (−2300–100bp) were extracted from the EPD website ( ) accessed on 28 September 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Then, cells were incubated for 24 hours in CO 2 incubator with 5% CO 2 . 11 2.3.4 Selection of transfected cells. For selection of transfected cells DMEM media was prepared by adding 200 mg mL −1 of hygromycin B.…”
Section: -(3-(2-hydroxyphenylmentioning
confidence: 99%
“…The most common approach for solving this problem is two single promoter in series to form a dual promoter system. [15][16][17][18][19] Finn et al studies showed that the dual promoter can effectively increase the gene expression level with non-viral vector. 20 Thus it is more important in clinical application.…”
Section: Introductionmentioning
confidence: 99%